Dentigerous cyst or ameloblastoma? Importance of histological analysis in the diagnosis of these pathologies. - Tovío-Martínez, Eilien (2020)
Dentigerous cysts and ameloblastomas present with few symptoms, and clinical characteristics present when lesions reach larger dimensions following a considerable length of evolution, and thus, these lesions are often discovered in routine radiographic examinations. This studydescribes the histological findings and clinical, pathological, and radiographic correlations between dentigerous cysts and ameloblastomas which aid in diagnosis and treatment planning. Two male patients, aged 12 and 15, were attended at the Faculty of Dentistry of the CartagenaUniversity in Colombia due to swelling at the mandibular symphysis and lower right third molar area. The clinical, radiographic and histological findings are described. Clinical and radiographic findings must be taken into account to diagnose dentigerous cysts and ameloblastomas, withhistopathological examination providing the definitive diagnosis and allowing adequate patient management.